2020
DOI: 10.1002/acr.24012
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Message Framing on Patients’ Perceptions and Willingness to Change to a Biosimilar in a Hypothetical Drug Switch

Abstract: Objective Patients often hold negative perceptions toward biosimilars that can create barriers to their uptake. Physicians also report uncertainty in how best to explain biosimilars. The aim of this study was to measure the effect of differently framed explanations on patients’ perceptions of and willingness to change to a biosimilar in a hypothetical drug switch. Methods Ninety‐six patients with rheumatic diseases taking an originator biologic were randomized to receive 1 of 4 biosimilar explanations: positiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 40 publications
(50 reference statements)
1
33
0
1
Order By: Relevance
“…We found that the patients likely to refuse biosimilars tended to be older and more likely to refuse generic medicines, mirroring the findings of the French cohort . It could be particularly valuable to provide these patients with reassuring and positive framing about biosimilars, as this has been demonstrated to increase patient acceptance of these medicines and to reduce the nocebo effect . Although there are distinct differences between generics and biosimilars, it is likely that some patients extrapolate their negative perception of generic medicines to the biosimilar.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…We found that the patients likely to refuse biosimilars tended to be older and more likely to refuse generic medicines, mirroring the findings of the French cohort . It could be particularly valuable to provide these patients with reassuring and positive framing about biosimilars, as this has been demonstrated to increase patient acceptance of these medicines and to reduce the nocebo effect . Although there are distinct differences between generics and biosimilars, it is likely that some patients extrapolate their negative perception of generic medicines to the biosimilar.…”
Section: Discussionsupporting
confidence: 67%
“…5 It could be particularly valuable to provide these patients with reassuring and positive framing about biosimilars, as this has been demonstrated to increase patient acceptance of these medicines and to reduce the nocebo effect. 9,10 Although there are distinct differences between generics and biosimilars, it is likely that some patients extrapolate their negative perception of generic medicines to the biosimilar. The commonest reason for biosimilar nonacceptance was concern regarding loss of efficacy, suggesting patients may feel apprehensive when switching from a bio-originator to a biosimilar.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have already shown that it is crucial to positively formulate the message about biosimilars towards patients. An empathic and positive communication (including positive framing) or attitude increase the acceptance to switch and reduce the development of nocebo effects after transitioning to a biosimilar [54][55][56][57][58]. An open and positive communication, emphasizing the equalities and not the differences between the reference product and its biosimilar, should be the norm when talking to patients.…”
Section: Communicate Positivelymentioning
confidence: 99%
“…As cited previously, one example is that biosimilars are highly similar but not identical to their reference products, which can be understood as implying a difference of some sort. The impact of message framing on biosimilar use was evaluated in a recent study that compared patient responses to a hypothetical switch from a reference biologic to a biosimilar that was accompanied with either positive or negative framing [ 40 ]. The authors found a greater patient willingness to switch to a biosimilar if the switch was explained to them by physicians (1) who emphasized the similarities between reference product and biosimilar and (2) who used positive body language and verbal cues to promote a positive interaction.…”
Section: Types Of Biosimilar Disparagement and Misinformationmentioning
confidence: 99%